2011
DOI: 10.4103/1463-1741.82959
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise, annoyance and community health survey - A case study for an Indian city

Abstract: The present study is aimed to investigate the impact of noise pollution on residents/community residing near roadside. The degree of annoyance was assessed by means of a questionnaire. It was found that among all noise-generating sources, road traffic was the major source of noise followed by factory/machines. A health survey reported about 52% of population was suffering by frequent irritation. 46% respondent felt hypertension, and 48.6% observed loss of sleep due to noise pollution. Common noise descriptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Studies assessing noise levels in different settings, week day and holidays, and different zones observed that average noise levels were above the permissible standards. (12131415) Another convenient mode of transport in urban areas, the metro trains, were found to generate noise levels, above the permissible levels of 65 dBA (day) and 55 dBA (night) (commercial zone). (16) Although the ambient noise level is reduced due to its predominant underground location, workers are at higher risk, particularly those stationed at the high noise level areas (engine noise, electric generator etc.…”
Section: Magnitude Of Community Noise Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies assessing noise levels in different settings, week day and holidays, and different zones observed that average noise levels were above the permissible standards. (12131415) Another convenient mode of transport in urban areas, the metro trains, were found to generate noise levels, above the permissible levels of 65 dBA (day) and 55 dBA (night) (commercial zone). (16) Although the ambient noise level is reduced due to its predominant underground location, workers are at higher risk, particularly those stationed at the high noise level areas (engine noise, electric generator etc.…”
Section: Magnitude Of Community Noise Pollutionmentioning
confidence: 99%
“…(9) Residents living near roadways reported frequent irritation (52%), hypertension (46%), and loss of sleep (48.6%) due to noise pollution. (15) Sleep is disturbed when indoor noise levels are above 30 dB, and 45 dB for sleeping outdoors. After-effects of sleep disturbance include headache and inability of concentrate in one's work and irritability.…”
Section: Magnitude Of Community Noise Pollutionmentioning
confidence: 99%
“…In addition to light, environmental noise may disturb sleep. Several recent studies have demonstrated that loud noises at night interfere with sleep [188][189][190][191][192][193][194][195]. For example, Basner and colleagues found that sound at 45 dBA increased the likelihood of sleep state change by about 50 % and EEG arousal by about 85 %, and noise at 65 dBA was associated with an approximately fourfold increase in the likelihood of a sleep state change or EEG arousal, as well as awakenings.…”
Section: Physical Environmentmentioning
confidence: 99%
“…The frequent honking behaviour of vehicle drivers which is associated with traffic congestion is a major source of noise pollution in cities [48]. Noise from horns is the sonic expression of the presence of traffic congestion.…”
Section: H Indexmentioning
confidence: 99%